PENGARUH KARAKTERISTIK MULTINASIONALITAS DAN THIN CAPITALIZATION TERHADAP EFFECTIVE TAX RATE - Hari Hananto (Jurusan Akuntansi,Fakultas Bisnis dan Ekonomika,Universitas Surabaya, 2021)
The company always tries to minimize tax payments through various ways. In particular, a multinational company, has more ability to do tax avoidance. One technique that can be used by multinational corporations is to transfer corporate income from one jurisdiction to another that has a lower corporate income tax rate to minimize overall group tax payments. This mechanism can result in superior tax payments for multinational companies that have subsidiaries or affiliated companies. In addition to income transfer, multinational companies can also regulate their capital composition in order to take advantage of the ease of obtaining capital in a jurisdiction. This study aims to show empirical evidence about the effect of the nature of multinationality (multinational companies) and the existence of capitalization (thin capitalization) on the possibility of tax avoidance. The population sample used in this study were companies listed on the IDX during the 2017-2019 period. The results show that multinational companies have an effect on increasing tax avoidance efforts. Meanwhile, thin capitalization has no effect on efforts to increase tax avoidance.